APPLICATION OF FUZZY LOGIC IN DETERMINING THE AMOUNT OF COTO PRODUCTION AT THE COTO DAENG TATA WARUNG USING FUZZY LOGIC BASED ON THE TSUKAMOTO METHOD - Ayu Irdayanti.J; Andi Azizul Hakim; Suci Permatasari; marwan (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2024)
This research focuses on enhancing Coto production efficiency at Warung Coto Daeng Tata through the application of fuzzy logic, specifically utilizing the Tsukamoto method. Challenges such as unpredictable demand fluctuations and inconsistent raw material variations hinder production adaptation. However, by refining fuzzy rules based on shop experience and adjusting parameters, this study aims to optimize responses to market changes and customer demands. Method stages encompass establishing fuzzy rules, fuzzification, inference, and defuzzification, yielding adaptive production quantities. Results demonstrate the effectiveness of the Tsukamoto method in optimizing Coto production, aligning with input variables like weather and seasons to minimize waste and enhance customer satisfaction. The application of fuzzy logic enhances responsiveness to market dynamics and customer preferences, potentially improving operational performance and sustaining traditional culinary businesses